THE EMPOWERMENT OF SOCIETY TO REALIZE URBAN FARMING THROUGH HORTICULTURAL VILLAGES: Jambangan Urban Village, Jambangan Sub-District, Surabaya City - Erna Haryanti; Dwie Retna Suryaningsih; Markus Patiung; Ristani Widya Inti; Cindy Sulistyowati; Ken William Ang (International Journal of Engagement and Empowerment, 2022)
Dedication of society by the team of the Faculty of Agriculture UWKS With the title: THE EMPOWERMENT OF SOCIETY TO REALIZE URBAN FARMING THROUGH HORTICULTURAL VILLAGES was carried out at neighborhood 01 and hamlet 05 Jambangan village, Jambangan sub-district, Surabaya, aim to motivate the society to carry out city agricultural activities that are more innovative and have economic value. So that the society will have new knowledge and skills that are implemented as productive activities and become a resource of family income. In detail the purpose of this society service are: a) Motivating horticultural cultured society b) Transferring science and technology on strategies to get business opportunities c) Developing new entrepreneurs, as well as the realization of a capable horticultural village and a pioneer for other villages. By applying the full participation method, providing chance and opportunities for the target, together with the team to synergize to arrange activity planning, organize, implement and evaluate this Penmas activity. The society and the local government responded well, to this society's dedication, it was seen from its enthusiasm and participation during the activity such as in terms of providing land for planting and contributing in the form of fertilizers, etc